2000
DOI: 10.1186/1297-9686-32-2-205
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic lipogenesis gene expression in two experimental egg-laying lines divergently selected on residual food consumption

Abstract: -Two Rhode Island Red egg-laying lines have been divergently selected on residual food intake (low intake R − line, high intake R + line) for 19 generations. In addition to direct response, correlated responses have altered several other traits such as carcass adiposity and lipid contents of several tissues, the R + animals being leaner than the R − ones. In a search for the biological origin of the differences observed in fat deposit, the hepatic mRNA amounts of genes involved in lipid metabolism were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
1
0
2
Order By: Relevance
“…Une sélection sur une faible consommation résiduelle chez la volaille entraîne une réduction de la production de chaleur de 20 à 30 %, associée à une réduction de la production de chaleur liée à l'utilisation de l'aliment et à l'activité physique, sans modification des performances (Gabarrou et al 1998). Comme pour la lignée de souris HP-, les poules pondeuses R-sont significativement plus grasses en raison notamment d'une augmentation de l'expression de gènes codant pour des enzymes lipogéniques (Lagarrigue et al 2000). La variabilité génétique de la consommation résiduelle chez le porc est relativement bien décrite dans la bibliographie.…”
Section: Indicateurs De La Production De Chaleurunclassified
“…Une sélection sur une faible consommation résiduelle chez la volaille entraîne une réduction de la production de chaleur de 20 à 30 %, associée à une réduction de la production de chaleur liée à l'utilisation de l'aliment et à l'activité physique, sans modification des performances (Gabarrou et al 1998). Comme pour la lignée de souris HP-, les poules pondeuses R-sont significativement plus grasses en raison notamment d'une augmentation de l'expression de gènes codant pour des enzymes lipogéniques (Lagarrigue et al 2000). La variabilité génétique de la consommation résiduelle chez le porc est relativement bien décrite dans la bibliographie.…”
Section: Indicateurs De La Production De Chaleurunclassified
“…Indeed, APOA1 is involved in the transport of triglycerides from liver cells to adipose tissues by taking part in the formation of HDL (high density lipoprotein). Lagarrigue et al [ 33 ] reported that the amounts of APOA1 mRNA were significantly larger in chickens from fat lines than from lean lines, which supported the hypothesis that it has a role in lipid transport and storage in birds. Szapacs et al [ 34 ] showed that when APOA1 was exposed to oxidative changes, the formation of HDL and its exportation to the liver were altered.…”
Section: Discussionmentioning
confidence: 83%
“…El presente estudio muestra una correlación positiva y significativa entre los niveles de colesterol total y colesterol HDL (P<0,05) en la línea Lohmann Brown-Classic; sin embargo, se observó una relación negativa no significativa en la línea Hy line W-36 (Cuadro 1). Esto se pudo haber debido a que las HDL son las encargadas de transportar el colesterol al hígado para su eliminación biliar (Lagarrigue et al 2000) o a la yema de huevo (Vieira et al 1995). Los niveles menores en suero de colesterol HDL y la relación negativa encontrada entre colesterol total y el colesterol HDL en la línea Hy-Line W-36 podrían indicar que esta línea, en la semana 26 de producción, tiene una menor cantidad de colesterol total disponible para la yema de huevo.…”
Section: Semana De Producciónunclassified